Representasi Orientalisme Dalam Film The Man Who Knew Infinity - Fildzah Nabilah Abrar; Anis Endang; Harius Eko Saputra (Professional: Jurnal Komunikasi dan Administrasi Publik, 2017)
Western unceasing production of the film with the character of the East that bad in it. To maintain the Orientalism of the West, adapt them to the times. Media of mass used is the mass media movie. Because of the film's West could easily represent Orientalism. The movie is popular and in demand, and can be watched by all ages. One Western movie that shows the representation of Orientalism is the movie The Man Who Knew Infinity. MovieThe Man Who Knew Infinity tells of the struggle of one of the Eastern scholars in the field of mathematics named Srinivasa Ramanujan. The movie represents the power and difference in social status between the West and the East. As well as how the Western view of the East or Orientalism.And to know the description or representation intentionally created by the movie, then the unambiguous approach to the Semiotic, to use Roland Barthes's model. So, this research want to find out how the meaning of denotation, connotation, and myth preformance of orientalism in the movie The Man Who Knew Infinity. Through the observation carefully and in collaboration with relevant documents, finally found the scene-the scene that can represent the orientalism in the film The Man Who Knew Infinity.The results showed that the representation of Orientalism that aredisplayed in the film this is a form of power of the West against the East. And the difference stastus social as well as position that are shown between the East and the West. Film director Matt Brown, accentuate how the West perceives the East. Although in the field of education of the East and the West have equality. But in class social status and position. The west and the East is not equal in the perspective of Orientalism.